5 - Quel plan Marshall pour l’Afrique ? - TEDAJO, J. (Africa Development, 1983)
The growing concern showed by international creditors about the debts of developing countries, the pervasiveness of this problem as well as the specific nature of economic and social problems of development with respect to the growing inadequacy of international aid and développent finan cing, make it necessary to reflect deeply on the concept of development, on the nature of the aid provided and on the general philosophy of inter national aid development. If, during the past few years of crisis some politicians have been led to apply for a «Marshall» type of aid to developing countries, an ana lysis of the aid to the reconstruction of Europe which was proposed by the Marshall plan, shows however that every precaution had been taken for the plan to be efficient. Despite the specific nature of the problem of development which is more serious than that of reconstruction, not only have the minimal conditions for,the efficiency of an «aid of restructuring» as opposed to an aid for reconstruction, not been met during the last two decades of deve lopment of the United Nations, but they have never been seriously debated at the regional level. Now, the existence of the Lagos Plan of Action at the African regional level provides us with a framework for debates. These de bates could help determine the conditions under which an aid to econo mic restructuring can be efficient. Therefore it is μρ to the partners of the industrialized countries, and particularly to the European ones, of Africa who deeply committed themselves to a new international economic order in the Lome Agreement, to study the ways and means of reorienting deve lopment aid and financing towards the objectives of development. J. TEDAJO est actuellement économiste au Centre Africain d'Etudes Monétaires, à Dakar/Sénégal Cet article, avait fait l'objet en 1978 d'une communication de l'auteur à la commission du groupe d'experts Européens sur les implications réciproques des politiques de coopération CÉE—PVD réuni à Bruxelles le 16 Juin 1978. R a été légèrement retouché pour tenir compte du Plan d'Action de Lagos adopté par les chefs d'Etat africains en 1980.